Does cooperative membership improve household welfare? Evidence from a panel data analysis of smallholder dairy farmers in Bihar, India - Kumar, Anjani; Saroj, Sunil; Takeshima, Hiroyuki; Joshi, Pramod Kumar (International Food Policy Research Institute, 2018)
The promotion of cooperatives is widely viewed as the most important institutional arrangement for spurring dairy development in India and much of the success of the White Revolution in India is attributed to the cooperative framework of the country's dairy development strategies. However, empirical evidences on impact of dairy cooperatives based on sound econometric analysis are scarce. To bridge the gap in literature, this paper examines the impact of dairy cooperative membership on farm performance indicators, such as milk yield, net returns, and adoption of food safety measures (FSM) in milk production, using panel data from a survey of milk producers in 2007 and 2015 in Bihar, India. An endogenous switching regression model, which accounts for selection bias, is used in the analysis.